A comparative study of the effect of capsular repair in the Latarjet procedure - Andrew P. McBride; Thibault Lafosse; Alex N. Karanja; Laurent Lafosse; Ian P. Hughes; Gregory A. Hoy; Eugene T. Ek; Shane A. Barwood; Fraser Taylor; Ezekiel Tan (BMC Musculoskeletal Disorders)
Abstract Background Long term studies have shown the Latarjet procedure to be successful in preventing re-dislocation in primary and recurrent anterior inferior shoulder instability. It provides stability through the sling effect of the conjoint tendon and the bone block. It is unclear whether augmentation with capsular repair provides an added benefit or leads to restricted range of external rotation. The primary aim of this study is to evaluate the effect of capsular repair in the open Latarjet procedure on rotational range of active external rotation in 90 degrees abduction (RoM-ER90). The secondary aim is to evaluate the effect on clinical outcomes including post-operative apprehension, instability, proprioception and shoulder function scores. Methods This is a multi-national retrospective cohort study including patients with a minimum of 6-months follow-up post Latarjet procedure performed between 2016 and 2020 recruited from 3 units in Australia and France. Range of motion was measured using a Proteck goniometer. Clinical outcomes were assessed using the Western Ontario Shoulder Instability Index (WOSI), Oxford shoulder, Oxford instability, Walch-Duplay and Rowe scores. Shoulder proprioception was assessed by the active relocation test described by Glendon et al. Results Forty-four patients were included, median age was 29.5 years and 91% male. Three groups were assessed, open latarjet with no capsular repair (OL n = 11), open latarjet with capsular repair (OLCR n = 20), and arthroscopic Latarjet without capsular repair (AL n = 13). There was no apparent effect of capsular repair on the ROM-ER 90 in the open groups with a median (interquartile range) of 78° (72°, 90°) for OL and 84° (75°, 90°; P = 0.87) for OLCR groups. Capsular repair and arthroscopic approach did not affect the proportion of patients reporting shoulder apprehension (P = 0.52 and 0.48 respectively). There was no difference in proprioception between operative and non-operative sides for the OL group (P = 0.43). Proprioception was poorer on the operative side for the OLCR group (P = 0.04) but better on the operative side for the AL group (P = 0.08). WOSI scores for the open surgical groups were similar (OL = 78, OLCR = 80, P = 0.91) and when combined (median WOSI = 79) demonstrated greater stability than the AL group (P = 0.009). There was no evidence of an effect of capsular repair or arthroscopic approach on the Walch-Duplay, Oxford Instability, or Rowe scores. Conclusions There is no significant difference in ROM-ER 90 or WOSI score in patients who undergo the Latarjet procedure with and without capsular repair. The arthroscopic Latarjet may preserve proprioception but did not improve shoulder stability compared to the open Latarjet. Level of evidence III, retrospective cohort study.